Elevated serum concentrations of IGF-1 and IGF-1R in patients with thyroid cancers - Hanna Lawnicka; Ewelina Motylewska; Magdalena Borkowska; Krzysztof Kuzdak; Agnieszka Siejka; Jacek Swietoslawski; Henryk Stepien; Tomasz Stepien (Biomedical Papers, 2020)
Background: The rising incidence of thyroid cancer observed in the last few decades requires an improvement in diagnostic tools and management techniques for patients with thyroid nodules. Aims: The aim of this study was to assess serum concentrations of IGF-1 and IGF-1R in patients diagnosed with thyroid cancers. Methods: 36 patients diagnosed with papillary thyroid cancer (PTC), 11 subjects with follicular thyroid cancer (FTC), 9 patients with anaplastic thyroid cancer (ATC) and 19 subjects with multinodular nontoxic goiter (MNG) were enrolled to the study. The control group (CG) consisted of 20 healthy volunteers. Blood samples were collected one day before surgery. Serum IGF-1 and IGF-1R concentrations were measured using specific ELISA methods. Results: Significantly higher concentrations of IGF-1 were found in patients with PTC as compared with controls but not that obtained from subjects diagnosed with MNG. The concentration of IGF-1R was significantly elevated in subjects with PTC and ATC as compared with healthy volunteers. Similarly, patients diagnosed with PTC or ATC presented significantly higher serum concentration of IGF-1R in comparison to the MNG group. Conclusions: Our results show that the IGF-1 - IGF-1R axis plays a significant role in the development of PTC and ATC and imply that serum concentrations of both cytokines may be considered as additional markers for the differentiation of malignancies during the preoperative diagnosis of patients with thyroid gland tumors. These results indicate that IGF-1R serum concentrations allow us to differentiate between MNG and PTC or ATC. Moreover IGF-1R serum values appear to be better predictor of PTC and ATC than IGF-1 concentrations.